Child Marriage as Structural and Ecological Violence: An Eco-Fiqh Critique of Indonesian Islamic Family Law - Mohammad Saiful Islam; Ranny Apriani Nusa; Gazali; Abdul Rahman Abd. Latief; Jihan Safira (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Child marriage remains a persistent socio-legal issue in Indonesia, reflecting not only cultural and economic pressures but also deeper forms of structural and ecological violence. This study aims to critically examine child marriage through the lens of eco-fiqh, an integrative Islamic legal perspective that emphasizes the interconnectedness between human well-being, social justice, and environmental sustainability. Using a qualitative normative approach, this research analyzes Indonesian Islamic family law alongside relevant socio-ecological frameworks. The findings reveal that child marriage perpetuates structural violence by reinforcing gender inequality, limiting access to education, and sustaining cycles of poverty. Moreover, it embodies ecological violence by disrupting the balance of social and environmental systems, particularly in vulnerable communities where early marriage correlates with overpopulation, resource strain, and diminished resilience. From an eco-fiqh perspective, such practices contradict the maq??id al-shar?‘ah, especially the protection of life (?if? al-nafs), intellect (?if? al-‘aql), and progeny (?if? al-nasl). This study argues that Indonesian Islamic family law must be reinterpreted and reformed to incorporate eco-justice principles, promoting a more holistic understanding of harm and welfare. Strengthening legal frameworks, enhancing community awareness, and integrating eco-fiqh values into policy discourse are essential steps toward eliminating child marriage and fostering sustainable social development.